Perjanjian Kawin yang Tidak Didaftarkan dalam Perkawinan Campuran - Desak Putu Kania Pratiwi; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Konstruksi Hukum, 2020)
Humans are naturally born as individual and social beings, destined to have a life partner to have offspring and made a happy family. In marriages, both marriages between countries or different nationalities have legal problems regarding injustice in exercising the rights and obligations of the husband or wife. The existence of a marriage promise is very important to protect these rights and obligations. This research explains how legal the status of the marriage agreement in marriage and the responsiveness the law of an agreement that is not registered. This research used normative legal research and analysis uses interpretative, systematic, and argumentative methods. Sources of data in this study are sources of primary and secondary legal materials. The result of the research is the legal position of the marriage agreement in mixed marriages, which is to provide legal certainty in carrying out legal actions on assets under control, either inherited or acquired after or during marriage, as well as providing protection for the rights and obligations of each party in managing the house stairs. Second, the legal consequence of a marriage agreement that does not register in a mixed marriage is that the marriage agreement is still binding on both parties, but the marriage agreement does not bind a third party or there is a legal action committed against the property under their respective control.